Полная энциклопедия камней и амулетов - Белов Николай Владимирович (АСТ, 2006)
Экземпляры: аб. ЦБ (20200323) / Инвентарный номер: 9021 / Цена: / Сис.шифр: 86.4 / Авт.знак: П 51 / ГРНТИ: 21.15.69 / ББК: 86.41